Narrative Gerontology, Spiritual Time - Achenbaum, W. Andrew; Lewis, Barbara (Narrative Works, 2012)
Editor’s Introduction William L. Randall, St. Thomas University No doubt, we each have a story about how we first got interested in narrative. For some of us, it was a chance meeting with a colleague whose enthusiasm for the topic we gradually came to share. For others, it was stumbling onto a book by Kenneth Plummer or Jerome Bruner, by Rita Charon or Ivor Goodson, by Michael White and David Epston or Michael Connelly and Jean Clandinin, that got us thinking, “Hey, it’s all about stories!” As for my own story, while a student in divinity school in the mid-1970s, I was assigned to work one summer with the Reverend Ian Lynk, a Protestant minister in suburban Montreal. My job was to shadow him around while he visited his parishioners and dispensed his pastoral tasks. Earlier that year, however, he had taken a course at New York’s Union Seminary taught by Old Testament scholar,James Sanders, who had infected him with an interest in something Sanders and others were calling narrative theology. A core insight of narrative theology is that the Bible as a whole is less a collection of sacred edicts and timeless truths than a sprawling collage of narrative material—compiled by different redactors at different times—that takes in everything from myth to legend, chronicle to biography, and parable to dream. Moreover, the process of coming to belief entails the internalization of a master narrative which the scriptures sketch for us about where we have come from, where we are headed, and how we should behave in the interim—a grand story, if you will, with a Beginning, Middle, and End and with immense moral- cosmological weight. As such, sharing one’s faith with others involves telling one’s own personalized version of that grand story in the hopes that they “convert” to it and find their lives grounded and guided accordingly. Ian’s infection having infected me in turn, I returned to Toronto at the end of the summer for my final year of studies, and embarked upon a kind of senior thesis that I entitled “My Story, Our Story, and The Story: Towards a Narrative Theology.” In the course of preparing it, I discovered the work of American theologian, H. Richard Niebuhr (1941), whose book The Meaning of Revelation(especially his distinction between “outside story” and “inside story”) was a turning-point in my own thinking, plus the writings of other theologians who brought a narrative perspective to the topic of “faith”—people like Stanley Hauerwas (1977), Sally Teselle (1975), and Robert McAfee Brown (1975). The following year, while pursuing further studies at Cambridge, I was assigned Don Cupitt as my tutor. At the time, Don was Dean of Emmanuel College and author of (among many works, then and since) a volume entitled simply What Is a Story? (1991). In it, he engages in a provocative deconstruction of the grand master narrative of Christianity and examines the implications of such a critique for our self-understanding as people of faith. More recently, I’ve been thinking about the focus for my next major project, one in which I hope to weave together what, for the past 30 some years, have been the three main strands of my professional and intellectual life: theology, or more broadly spirituality;aging, which is my obvious focus as a gerontologist; and narrative. My hope is to articulate what I’m currently calling “a narrative theology of aging” (Randall, 2010). In this invited piece by Andrew Achenbaum, a member of the editorial board of this journal, and his partner Barbara Lewis, a similar sort of weaving may be seen. Achenbaum, a highly respected scholar who champions the importance of the humanities in the study of aging, has recently completed a biography of the late Robert Butler, geriatrician and gerontologist extraordinaire (Achenbaum, in press). Among Butler’s best-known publications is an article that appeared in the journal Psychiatry in 1963 entitled “The Life Review: An Interpretation of Reminiscence in the Aged.” Now widely regarded as a seminal contribution to the psychology of aging, the article builds on Erikson’s thinking about on the crisisof “Ego Integrity versus Despair” that faces us as we age to argue that pivotal to positive mental health in later life is a process of life review, i.e., stepping back from our lives and engaging in “narrative reflection” (Freeman, 2010) upon them, thereby (hopefully) achieving a sense of acceptance and affirmation of the particular path that our life course has taken. In what follows, Achenbaum and Lewis trace their own unique paths through the ups and downs of their respective lives: paths which led through different marriages and divorces, through various doubts and discoveries, and eventually to each other. In doing so, they weave an intriguing tale story about faith, about aging, and about love. One further story, if I may . . . One of the scholars whose work I discovered early in my journey into narrative was the late Stephen Crites. Formerly a professor of philosophy at Wesleyan University, his 1971 article entitled “The Narrative Quality of Experience” was for me, as for many, a ground-breaking piece of thinking which set my mind spinning with all sorts of delicious questions about the storied dimensions of religious conviction in particular and the narrative complexity of human life in general. In May 2002, I had the privilege of chatting with Crites in person over lunch one day during the first conference called Narrative Matters, a series of biennial interdisciplinary events which, with my colleague Dolores Furlong of the University of New Brunswick, I had a hand in starting. It was one of those meetings I’ll never forget, and one of those stories I tend to trot out when asked how I got into narrative in the first place. A kindly gentleman with a soft sense of humour and the unusual talent for actually listening to what you had to say, Crites—then in his 70s—had driven to New Brunswick, by himself, from his home in Connecticut, not as an invited speaker but as an ordinary delegate, to deliver a touching little paper entitled simply “A Love Story” (Crites, 2002). In it, drawing deeply on his own life story—as so many of us narrativists, explicitly or otherwise and regardless of our field, invariably do—he wove together a rich range of insights into faith and life and love; especially first love, reflected back on from the poignant vantage point of later life. It is just such sorts of insights that Achenbaum and Lewis have sought to capture for us here. References Achenbaum, A. (In press). Robert N. Butler: Visionary of healthy aging. New York, NY: Columbia University Press. Brown, R. (1975). My story and “the story.” Theology Today, 32(2), 166-173. Butler, R. (1963). The life review: An interpretation of reminiscence in the aged. Psychiatry, 26, 65-76. Crites, S. (1971). The narrative quality of experience. Journal of the American Academy of Religion, 39(3), 291-311. Crites, S. (2002, May). A love story. Paper presented at Narrative Matters 2002, Fredericton, New Brunswick, Canada. Cupitt, D. (1991). What is a story? London, UK: SCM. Freeman, M. (2010). Hindsight: The promise and peril of looking backward. New York, NY: Oxford University Press. Hauerwas, S. (1977). Truthfulness and tragedy: Further investigations into Christian ethics. Notre Dame, IN: University of Notre Dame Press. Niebuhr, H. R. (1941). The meaning of revelation. New York, NY: Macmillan. Randall, W. (2010, May). Open stories, open lives: Toward a narrative theology of aging. Paper at Narrative Matters 2010, Fredericton, New Brunswick, Canada. TeSelle, S. (1975). Speaking in parables: A study in metaphor and theology. Philadelphia, PA: Fortress Press.